(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
T – H Indian Government made a high-chance, high-stakes financial mediation on the world’s biggest Democratic state, with a goal to diminish corruption from the country. Overnight, 86% of cash trade flow was voided. Nation’s right around 90% cash money dependent were disturbed due to the ban of certain currency th notes which resulted in Demonetization after 25 years of economic reforms that changes many paradigms in the Indian nation not only in terms of economically but also affected many other domain areas like lifestyle, health, infrastructure and the fourth pillar of the society i.e. media and entertainment sector too. The Blame game as well as the games to build the positive aura to fill the scars of demonetization started via use of the effective tool called New media specially using the hash tags i.e. Twitter. As we know social media is a game changer in the political campaigns, it also helped the country during the demonetization period. The communication skills on twitter have come into sharp focus in the past three to four months during the self created crisis of the government, when they rendered Rs. 500 and Rs. 1000 notes. Despite of several criticisms from the public and the other political parties of the hardship caused by the demonetization process around 90% of the population supported this move. The study is all about how the new media especially the twitter helps created the positive aura to the masses and specially the citizen of republic of India or not during the demonetization period when there was hustle bustle everywhere. The study will also deals with different analyses of the tweets done at the time of demonetization phase